Data-driven insights into interhospital care fragmentation: Implications for health policy and equity among older adults. - Somayeh Ghazalbash; Manaf Zargoush; Vedat Verter; Dan Perri (PLoS ONE)
Objective To determine factors leading to interhospital care fragmentation (ICF); evaluate how ICF affects rehospitalization costs, length of stays (LOS), and delayed discharge; and analyze ICF disparity among equity-seeking groups. Materials and methods We used a 13-year retrospective cohort of older adults (65+) in Ontario, Canada. Utilizing multivariable logistic regression, we identified characteristics associated with ICF and determined its association with outcomes. Results Discharge to facilities except home and homecare and travel distance were the strongest risk factors for ICF. Patients were less likely to experience ICF if they were older, frail, or had multiple comorbidities. ICF was strongly associated with an increase in the daily costs of readmission. Moreover, the risks of a prolonged LOS after ICF and delayed discharge were higher among returning surgical patients. The rural residency was a source of health inequality. Conclusions ICF exacerbates health disparities and worsens patient outcomes. Our study identified several risk factors associated with ICF, some of which are controllable, paving the way for interventions to mitigate this issue. To promote health equity and reduce adverse outcomes, policymakers should focus on policies for reducing care discontinuity, particularly addressing the controllable risk factors.